The Limits of Indicators of Wealth and Poverty through the Prism of a Systemic Approach of Zakatable Assets - Abderrazak Belabes (International Journal of Zakat, 2020)
The aim of the study is to explore the limitations of financial indicators of wealth and poverty in the light of a systemic approach which considers zakat assets as a system composed of parts that can interact with each other beyond first appearances. This allows human communities to attract what is beneficial and repel what is harmful in all circumstances, especially in times of crises and pandemics. Among the most important results reached by the study: the need to design indicators that are not only based on the quantity of money held by people, to highlight the quantities, volumes, sizes and areas related to resources to preserve the diversity of living things and ecosystems. The study recommends rehabilitation of the role of local actors in the design of indicators so that they are not the exclusive prerogative of international experts who are far removed from the daily concerns. This promotes freedom of initiative in the governance of local affairs in favour of the ‘de-financialization’ of human life.